Accessibility and feasibility of using technology to support mindfulness practice, reduce stress and promote long term mental health. (November 2018) - Burnett-Zeigler, Inger E.; Waldron, Elizabeth M.; Hong, Sunghyun; Yang, Amy; Wisner, Katherine L.; Ciolino, Jody D.
Abstract: Background and purpose: We evaluated the feasibility of using an activity monitor to support mindfulness practice, reduce self-reported stress and physiological indicators of stress. Materials and methods: Adult women (N = 19) who previously participated in a mindfulness intervention wore an activity monitor for eight-weeks. The activity monitor notified them when they were stressed (based on standard deviation pulse pressure). Heart rate and pulse pressure were continuously collected via the activity monitor. Mindfulness, stress, depression and trauma symptoms were collected via self-report surveys. Results: There were no significant changes in self-reported stress, depression, post-traumatic stress and mindfulness from baseline to eight-weeks. Pulse pressure and standard deviation of pulse pressure increased over time. Those who were high on the non-judge mindfulness subscale had a lower standard deviation pulse pressure and spent less time stressed. Conclusion: Those who are more mindful are less likely to have physiological signs of stress. Highlights: Those who are more mindful are less likely to have physiological signs of stress. Depression is positively associated with the percent of time stressed. Participants faced challenges in using the wrist worn activity monitor device. Additional research is needed to explore how technology can support mindfulness skills.